Evaluation of the effect of different commercial mouthrinses on the viability and activity of microcosm biofilm and on enamel demineralization - Braga, Aline Silva (2017)
The aim of this study was to evaluate the antimicrobial and anticaries effects of different commercial mouthrinses. The first chapter is about a review of literature whose the aim was to discuss the antimicrobial potential of different mouthrinses in respect to the control of dental caries and periodontal disease. The search of papers was conducted using PubMed and the keywords: \"antimicrobial agent\" or \"antiplaque agent,\" \"dental biofilm\" and \"dental caries\" or \"periodontal disease\" or \"gingivitis\". We found a total of 22 papers (2011-2015). The main active agents tested were: CHXChlorhexidine, CPC-cetylpyridinium chloride and EO-Essential oils (alcohol/or alcohol-free). CHX was compared to EO in 6 studies, showing superiority in 3 studies, similarity in 1 study and inferiority in 2 studies. CPC has shown lower effect in plaque reduction compared to CHX and EO. More clinical studies are needed for better understanding the mechanism of action and the differences in performance among the antiplaque agents. The second chapter has as aim to compare the antimicrobial and anticaries effects of six commercial mouthrinses (PerioGard®, Noplak® Max, Oral-B® Complete, Listerine® Zero, Malvatricin® Plus and Cepacol® Plus Advanced) under a microcosm biofilm model formed on enamel. A microcosm biofilm was produced on bovine enamel, using inoculum from pooled human saliva mixture with McBain saliva (with 0.2% sucrose), for 14 days. The biofilm was treated with the mouthrinses daily (1 min). The bacterial viability (% death), lactic acid production (mmol/l), the colony-forming unit (CFU) counting for total microorganisms, lactobacilli, total streptococci and mutans streptococci (log10 CFU/mL) and the extracellular polysaccharides production (EPS, mg/g) were quantified in the biofilm. The degree of enamel demineralization was analyzed using transverse microradiography-TMR (%min vol. m). Oral-B® Complete, Listerine® Zero and Malvatricin® Plus had the greatest effect on the reduction of biofilm viability (69-75% dead cells vs. 13% in the control, p<0.0001). On the other hand, the lactic acid production was significantly reduced by PerioGard®, Noplak® Max and Listerine® Zero compared to control (69% reduction, p<0.0001). There were no significant differences among the mouthrinses in respect to the CFU counting and EPS production. The enamel demineralization was significantly reduced by PerioGard®, Noplak® Max and Malvatricin® Plus compared to control (74% reduction, p<0.0001). Therefore, the commercial mouthrinses have different antimicrobial and anticaries effects. The mouthrinses containing chlorexidine or Malva sylvestris (with F, triclosan and xylitol) had the best anticaries effect under this model.